STUDI PENGGUNAAN KMnO4 UNTUK MEMPERPANJANG UMUR SIMPAN PISANG MULI - Ani Dahli; Agus Haryanto; Diding Suhandy (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2016)
The purpose of this research is to investigate the influence of KMn Asoxidizingethylene and to evaluate theeffective of KMn to extend the shelf life of bananas. This research was conductedusing a single treatment with fourlevels of giving mass that is 1 g, 5g, 10g, and a control without KMn, with ranges of banana’s weight was 400g.The result of the research showing that KMnasan oxidizingethylenebythe carrierfroma mixture of clayandricehusk ashin the storage ofbananas has positive influencein the process ofstorage. The most effective treatment is5 gram satseven days of shelf life and KMn which is placed beside the material is not effectively used because itcan not completely absorbethylene.Keywords : KMnO4, banana, ethylene, clay, shelf life.